AB0022 Cytotoxic profile characterization of nk and nkt cells in patients with behÇet disease. (15th June 2017) - Bonacini, M; Soriano, A; Calò, E; Zerbini, A; Cimino, L; Fontana, L; Parmeggiani, M; Salvarani, C; Croci, S
Abstract : Background: Behçhet disease (BD) is a rare inflammatory small vessel vasculitis. It is a chronic systemic disorder with multiorgan damage and various clinical manifestations such as oral ulcers, genital ulcers and uveitis. Etiology is still unknown. Some gene polymorphisms have been associated with BD [1]. In addition, a high frequency of circulating Natural Killer T cells (NKT cells) has been found in BD patients respect to patients with other inflammatory uveitis such as Vogt-Koyanagi-Harada disease (VKH) [2]. Objectives: The objective of this study was to characterize the cytotoxic profile of circulating Nautral Killer (NK) and NKT cells in BD patients. Methods: Peripheral Blood Mononuclear Cells (PBMCs) were collected from 23 BD patients (according to 1990 ISGB criteria), 7 VKH patients (according to 2001 Revised Diagnostic Criteria) and 9 healthy subjects [3, 4]. BD activity was evaluated with BD Current Activity Form 2003. Anti-CD56 and anti-CD3 antibodies were used to identify NK (CD56 + CD3 - ) and NKT (CD56 + CD3 + ) cells by flow-cytometry. Expression of one inhibiting receptor (NKG2A) and five activating receptors (CD16, CD69, NKG2D, Nkp30 and Nkp46) was determined on the surface of NK and NKT cells. Cytotoxic potential of NK and NKT cells was assessed through incubation of PBMCs with K526 cells in presence or absence of IL-15 followed by flow-cytometry detection of the surface marker CD107a on NK and NKT cells [5]. Results: A higher frequency of NKT cells was detected in peripheral blood of BD patients than VKH patients. Compared to healthy subjects, an increased proportion of CD16 positive NKT cells was found in BD patients. Furthermore it was observed a higher percentage of NKG2D positive cells in both NK and NKT lymphocytes. No difference in the other markers was detected. In BD patients, the incubation of PBMCs with K562 cells in absence of IL-15 induced a higher percentage of NK cells expressing CD107a compared to VKH patients. Frequency of CD107a positive NKT cells was <1% and similar between groups. Finally, no differences were found between BD patients with active and inactive phase of the disease. Conclusions: Our study confirms previous reports about an increased level of NKT cells in peripheral blood of BD patients, but we additionally identified a cytotoxic profile of NK and NKT cells characteristic of BD patients when compared to healthy subjects and patients with VKH. Our data revealed for the first time a potential involvement of NKG2D in the pathogenesis of BD. We can speculate that NK and NKT cells of BD patients are more prone to respond to stress/danger signals when exposed on target cells leading to cyclic auto-inflammation. References: Ombrello MJ. Et al. Proc Natl Acad Sci U S A. 2014, 111:8867–72. Hamzaoui K. et al. J Neuroimmunol. 2006, 175:160–8. International Study Group for Behçet's Disease. Lancet 1990, 335:1078–80. Read RW. et al. Am J Ophtalmol. 2001, 131:647–52. Alter G. et al. J Immunol Methods. 2004, 294:15–22. Disclosure of Interest: None declared